Discurso(s) acerca do trabalho presente nos livros didáticos de Geografia (1889-1945): educação, estado e ideologia - Elaine Queiroz Silva (2015)
During the transition from the imperial period for the Republican period, in Brazil there are transformations that have reached all the social and economic dynamics of the country. This context was characterized by a new organization of society, with the reconfiguration of work regime of the slave to free wage; the arrival of mass immigrants to the labor replacement and the emergence of the embryo of a national industrial production. These changes group reflected in the educational field. At this juncture, education promoted the adaptation of young people to new republican reality and the new form of work organization, spreading the ideologies of nation, civilization and progress. Several changes were made so that education could fulfill such a role, though this still remained a privilege of the dominant classes, who held private institutions and also availed themselves of the State to establish a public education that favor. To deepen the analysis of changes in education, the textbook presents itself as a potential major source as load speeches that were passed more than one generation. Due to its importance as a provider of information and ideologies, currently, the textbook has risen as material and focus of research for understanding the dynamics and various functions associated with school subjects. Based on this concept, this research will be analyzed Geography textbooks adopted and / or written by the College Pedro II teachers (Rio de Janeiro - RJ - founded in 1837). The centrality of research in this school and therefore textbooks related to it, is due to the importance of the institution, which served as a model for the national secondary education throughout the period considered in this analysis. The analysis of books seek to answer the following concerns: What speeches about the work are present in Geography textbooks used / written by the College Pedro II teachers in the period 1889 to 1945? What is the relationship between the discourse on this work in textbooks, changes in labor reality in the analysis context and the construction of the school geographical thought? As methodological approach, we have adopted the documentary research to contextualize about work, teaching and geography education as well as for the selection of books. In order to we make the analysis of, we use assumptions of Critical Discourse Analysis. We understand that the discursive practices bear the marks of tensions occurred in your production environment, revealing social values that human action thought important at that time. We consider then the textbooks as a discursive practice, based on the assumptions that the social nature of discourse is its most essential characteristic and that its role is crucial in the construction of social reality.